STUDY ON INFLUENCE OF LOW TEMPERATURE ENVIRONMENT ON FATIGUE CRACK GROWTH PERFORMANCE OF HIGH-SPEED RAILWAY BRAKE DISC MATEREIAL - DING SiYuan; MA Lei; SHI HanBo; PAN JunLin; YUAN HaiBing (Jixie qiangdu)
In order to study the effect of low temperature environment on the fatigue crack growth performance of high-speed train brake disc materials, the tensile and fatigue crack growth rate tests of special cast steel materials of high-speed railway brake disc at-40℃,-20℃, 0℃ and room temperature（20℃）were carried out. The mechanical properties, fatigue crack growth rate and fracture morphology of high-speed railway brake disc materials at different temperatures were analyzed. The results show that the decrease of temperature has a significant effect on the mechanical properties and fatigue crack propagation of high-speed railway brake disc. Compared with room temperature, the elastic modulus, Poisson′s ratio, yield strength, tensile strength and other mechanical properties of high-speed railway brake disc materials increase with the decrease of temperature. In the stable stage of fatigue crack growth, the fatigue crack growth rate decreases with the decrease of temperature, but the inhibition effect of low temperature on the fatigue crack growth rate decreases with the increase of ΔK. The fracture analysis shows that with the decrease of temperature, the fatigue crack propagation is likely to change from ductile fracture to brittle fracture.